Analisis Kriminologis terhadap Pemanfaatan Alat Polygraph dalam Mendukung Penyidikan Tindak Pidana di Laboratorium Forensik Polda Riau - Fahlewi, Khotma Umniah; Riky Novarizal (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2026)
This study aims to analyze the use of polygraph as a supporting tool in criminal investigations at the Forensic Laboratory (Bidlabfor) of the Riau Regional Police from a criminological perspective. This research used a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving investigators and forensic analysts selected through purposive sampling. The results show that the polygraph is used to detect deception through physiological responses such as heart rate, blood pressure, and respiration. It assists investigators in assessing the consistency of statements, especially in cases with limited physical evidence. However, its effectiveness is influenced by technical factors, psychological conditions of the subject, examination environment, and examiner competence. The findings also indicate that polygraph is effective as a supporting tool but cannot be used as primary legal evidence in the criminal justice system. This study concludes that polygraph serves as a scientific supporting tool in criminal investigations, but requires stronger regulations, standardized procedures, and improved human resource capacity.